(untitled) (The International Journal of Educational Sciences and Arts, 2023)
Team conflict is an important factor that profoundly affects the competition and training process. Among the many factors affecting the competition and training effect, team conflict has always been ignored. In sports teams, team members have a high degree of interdependence, and members interact frequently and need to trust each other to achieve success. Trust, as the basis and premise of cooperation among sports team members, promotes the coordination between team members, and reduces team conflicts. Furthermore, it creates excellent team performance. In the realm of sports teams, scholars’ attention to group sports forms the basis for understanding organizational structures, shared goals, and the need for a high degree of trust. The classification of job interdependence further delineates the collaborative nature within sports teams. The intricate relationship between team trust and team conflict is examined, shedding light on the pivotal role of trust in fostering communication, reducing conflicts, and encouraging alignment towards common goals. Thus, the present review aims to provide a comprehensive understanding of the concepts of team, team trust, and team conflict, particularly in the context of sports teams. It also sheds light on the intricate relationships and dynamics within teams, aiming to contribute valuable insights to the fields of management science, sports organization, and team dynamics.